Lagochilascaríase Experimental em Camundongos A/J e B10.A - PRUDENTE, Mariana Félix de Souza (2006)
Lagochilascariasis is an infection caused by a parasite from the genus Lagochilascaris and the species is Lagochilascaris minor Leiper 1909 Campos et al (1992) described its experimental evolutive cycle using a model constituted by mice as intermediate hosts and by domestic cats as definitive hosts The availability of murine strains with different genetic characteristics has favored the study of host-parasite relationships which are crucial to the establishment of susceptibility or resistance to infection The aim of this work was to evaluate parasitological histological serological and survival parameters in experimental infection with L. minor in isogenic B10.A and A/J mice to compare the different responses and determine susceptibility or resistance to infection Isogenic B10.A and A/J mice were each inoculated with 2000 infecting L minor eggs using esophagian sonde Three infected mice and one non-infected mouse were sacrificed from 15 to 180 days after infection (DAI) aiming analysis Groups with 22 male B10.A mice and 19 A/J mice were inoculated and the percentage of survival was analyzed during one-year period After mice sacrifice and skin removal the quantity of subcutaneous and muscular nodules was determined Larvae removed from nodules were measured in length and width (Paçô e Campos 1998) The obtention of antigen from crude secreted and excreted products from L minor larvae and the detection of IgM IgG IgA and IgE antibodies were performed according to Freitas (2003)Fragments from lungs liver lymph nodes and spleen were fixed and processed by method of inclusion in paraffin and stained by hematoxiline-eosin Luna stain and Masson Tricrome stain The semi-quantitative analysis of intensity of the inflammatory process and characterization of cell types were performed The percentage of B10.A and A/J mice survival were 33,3% and 90% respectively A/J mice presented higher number of encysted larvae in the superficial subcutaneous tissue until 150 DAI Only at 45 and 60 DAI larvae removed from A/J mice were significantly bigger than larvae removed from B10.A mice The pattern of pulmonary lesions in both mice strains was characterized by focal inflammatory infiltrated forming granulomas with mononuclear cell predominance The A/J mice presented lower inflammatory intensity The liver spleen and lymph nodes presented inflammatory reactional aspect in both strains The seric levels of IgG from A/J and B10.A mice increased during infection with no difference between strains At 45 DAI B10.A mice presented high level of seric IgM and IgA against the antigens from secreted and excreted products (SE) from larvae While A/J mice presented high production of seric IgA against antigens from crude extract between 90 and 180 DAI There were not detected considerable levels of seric IgE in infected animals Analyzing these results we conclude that the pulmonary lesions and the survival percentage clearly demonstrated the different evolution of susceptible and resistant experimental infection in mice Relating the number of subcutaneous nodules size of encysted larvae serology and anatomopathological lesions of liver spleen and lymph nodes the differences found between Lagochilascariasis resistant and susceptible strains are discrete